Pembuatan Papan Nama GG pada Dusun Nipah Desa Sungai Rengas - Karolina, Sindi; Fauzan, Rizky; Novita, Novita; The, Trixie Agustina; Lestari, Mugi Ayu; Wibowo, Titik (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The background to this community service activity is based on the problem of the lack of physical arrangement of villages, especially Nipah Hamlet, Sungai Rengas Kapuas Village, which is a division of Sungai Rengas Village, marked by PERDA Number 8 of 2019. In this era, the development of village spatial planning is the main key in optimizing the potential of the area, because Rengas Kapuas Village is an expansion, there is still a lot of infrastructure that is still a concern for the local government, one of which is the gg name sign on each gg in Nipah hamlet. Due to the lack of gg signs in Nipah hamlet, in coordination with the hamlet and involving village officials and local residents in making gg signs, this was carried out. Activities will be carried out from July 1 to July 31 2024. Construction of Regional Boundary Nameplates consists of poles, nameplates and writing. The results of the KKN show that making gg nameplates is very beneficial for the residents of Nipah Hamlet, where residents feel satisfied because they have good environmental infrastructure and find it easier to find gg and can provide complete address information.